Dampak Kemasan Produk, Kualitas Bahan Baku dan Promosi di Media Sosial Terhadap Penjualan Produk Pink Lava di Surabaya - Ghoi, Maria Vianey; kusmayati, nindya kartika; Suwangsih, Iwang; Kurniawan, Taufik (Universitas Kadiri, 2023)
In conducting this research, the author’s goal was to see how big the Impact of Product Packaging, Quality of Raw Materials, and Promotion on Social Media on sales of Pink Lava Products in Surabaya, with a population of 120 people. The author also made the 120 respondents as samples in the study. Quantitative methods are defined in this study, with the main data collected through questionnaires and distributed to respondents using the Google form. The test was carried out using simple linear regression, and then an instrument test was carried out; the classical assumptions were continued by testing the hypothesis using the t-test. From the t-test results on the effect of product packaging on the quality of raw materials and promotion on social media on product sales, we get a linear regression form Y = 3.077 + 0.338X1 + 0.284X2 + 0.292 +e. From the results of linear regression, it was concluded that product packaging, quality, raw materials, and promotions on social media have a positive and relevant effect on sales of Pink Lava products in Surabaya